Gas chromatography–ion mobility spectrometry-based fingerprint analysis of volatile flavor compounds in ginger cultivated under different conditions - Qian-qian Jia; Jia-xing Li; Sen Yang; Ding-ding Su (Current Research in Food Science)
Ginger is widely acclaimed for its pungent aroma, nutritional benefits, and unique pharmacological properties, making it essential in culinary and medicinal applications. This study investigates volatile flavor profile differences in ginger resulting from various cultivation practices. Gas chromatography–ion mobility spectrometry (GC–IMS) was utilized to isolate and identify volatile compounds. Subsequent analyses, including relative odor activity values (ROAV) and multivariate statistical analysis, precisely identified key flavor compounds differentiating organically cultivated ginger from conventional field-grown varieties. A total of fifty-six volatile compounds were identified, comprising 17 esters, 4 alcohols, 7 ketones, 18 terpenoids, 6 aldehydes, and 4 miscellaneous compounds, with esters and terpenoids constituting over 50 % of total volatiles. Compounds such as α-phellandrene, β-citronellal, butyl 2-propenoate, 2-heptanone-D, and 3-octanone predominantly contributed lemon, banana, and citronella notes in organically cultivated ginger. In contrast, citral dominated in conventional ginger. This research significantly advances our understanding of ginger's aroma under varied cultivation conditions and demonstrates GC–IMS's utility in effectively profiling ginger flavor, thereby guiding improved cultivation and management.